Assessment of water quality and pollution load estimation in Marikina River using GIS in aid of developing a water quality management plan - Lipato, Glaiza Marie O.; Malenab, John Daniel D.; Resurreccion, Augustus C.; Macasieb, Reygie Q. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
In situ and laboratory analysis of water samples taken from the Marikina River is done to have a water quality data representative of the Marikina River Basin. Dissolved oxygen, temperature, total dissolved solids, and pH were determined in situ while turbidity, biochemical oxygen demand, chemical oxygen demand, and total suspended solids were determined from laboratory analysis. Water quality is assessed according to the water quality parameters of Department of Environment and Natural Resources Administrative Order. No. 2016-08 (DAO 2016-08), "Water Quality Guideline and General Effluent Standards of 2016." Unit load approach is used to estimate pollution load of point and nonpoint sources, where, the unit load is multiplied by the number of corresponding units per source. Point sources considered are domestic and industrial while agricultural and forest land use for non-point sources. A geographic information system (GIS) mapping software is utilized to produce visual presentations of the water quality assessment and pollution load estimation. Percent load reductions are proposed by comparing the results of the pollution load apportionment with allowable values from DAO 2016-08.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Water -- Pollution; Water quality -- Measurement